Chronic Cystoisospora belli infection in a Colombian patient living with HIV and poor adherence to highly active antiretroviral therapy (2021)
ABSTRACT : Cystoisospora belli is an intestinal Apicomplexan parasite associated with diarrheal illness and disseminated infections in humans, mainly immunocompromised individuals such as those living with the human immunodeficiency virus (HIV) or acquired immunodeficiency syndrome (AIDS). An irregular administration of highly active antiretroviral therapy (HAART) in HIV patients may increase the risk of opportunistic infections like cystoisosporiasis. We describe here a case of C. belli infection in a Colombian HIV patient with chronic gastrointestinal syndrome and poor adherence to HAART. His clinical and parasitological cure was achieved with trimethoprim-sulfamethoxazole treatment. Although a reduction in the number of C. belli cases has been observed since the use of HAART, this parasite still has to be considered as a differential diagnosis of diarrheal disease in HIV/AIDS patients. Effective interventions enhancing adherence to HAART should be included in HIV patient care programs.